INOVASI PENGOLAHAN UDANG MENJADI UDANG CRISPY SEBAGAI PRODUK UMKM DI DUSUN TANJUNG BERIKAT - Arif Rakhman; Iswandi; Karmila Sari; Bella Meliyana; Sefty Ameliya; Maulaya Maharani; Audy Cahaya Lestari; Ilham Fadilah; Riki Arjuni; Wisnu Wardana; Kevin Triansyah (Politeknik Negeri Sriwijaya, 2022)
Crispy shrimp is one of the products from shrimp processing that can be an alternative for people living on the coast to improve their economy. Community service activities carried out in Tanjung Berikat, Lubuk Besar District, Central Bangka Regency, Bangka Belitung Islands Province. This Real Work Lecture activity was carried out for 1 month with socialization and practical methods, starting from how to manufacture products to product marketing using existing social media. The purpose of the KKN program at the University of Muhammadiyah Bangka Belitung is to increase the added value of shrimp which is processed into crispy shrimp as an innovative product of UMKM in Tanjung Berikat.